Effects of Thermal Treatments on Physico-Chemical Properties and Antinutritional Factor Reductions of Sacha Inchi (Plukenetia volubilis L.) Meal - Suwanangul, Saranya; Jittrepotch, Nitipong; Ruttarattanamongkol, Khanitta (Naresuan University Journal: Science and Technology (NUJST); Vol 29 No 3 (2021): July-September 2021, 2021)
Sacha inchi seeds are normally used for the extraction of oil due to its high content of oil. The main by-product of the oil extraction process is the seed residue or meal, which is highly nutritious. However, the presence of naturally-occurring anti-nutritional factors (ANFs) especially phytate, tannins and trypsin inhibitors could limit the utilization of sacha inchi seed meal in foods and feeds. The aim of this study is to study the effects of thermal treatments including extrusion process (barrel temperature of 80, 90, 100°C and feed moisture of 61.8 %) and autoclaving (sterilizing temperature of 105, 110, 121°C for 30 min) of reduction of ANFs (tannins, phytic acid contents and trypsin inhibitor) and physico-chemical properties (water absorption index (WAI), water solubility index (WSI), protein solubility (PS), foam capacity (FC), emulsifying capacity (EC), emulsion stability (ES) and oil binding capacity (OBC)), antioxidant activities (ABTS •+ , FRAP assays and total phenolic content (TPC)) and in vitro protein digestibility of sacha inchi meal. The results show that autoclaving at 121°C for 30 min caused a significant (p<0.05) reduction in tannins (7.40 mg/g) and trypsin inhibitor (1.76 mg/g) compared to non-thermal treatment sample (control) (tannins =94.4 mg/g and trypsin inhibitor=8.52 mg/g). The phytic acid of non-thermal treatment sample (control) was significantly (p<0.05) decreased by extrusion at high barrel temperature of 100°C (0.43 mg/g). Furthermore, extrusion at barrel temperature of 100°C was the most effective in improving protein digestibility (55.8%). With an increase in temperature process of extrusion cooking and autoclaving, the WSI of treatment sample increased while the WAI decreased. An increase in barrel temperature enhanced the hydrophobicity of proteins as observed from the improvement of EC, ES, PS, FC and OBC values of the extruded samples. The barrel temperature of 100°C yielded highest EC (60.0%) ES (60.7%), PS (16.53%), FC (13.6%) and OBC (16.3%) in comparison with those of non-thermal treatment (control) (EC=46.5%, ES=37.0%, PS=5.48%, FC=4.90% and OBC=2.1%, respectively). The sample with extrusion at a lower temperature of 80°C possessed highest antioxidant activities indicated by ABTS •+ (2.34 mg Trolox /g powder), FRAP (1.07 mg FeSO 4 /g powder) and TPC (2.16 mg gallic acid/g powder). Overall, in vitro protein digestibility, antioxidant activities, antinutritional factor reduction and functional properties of sacha inchi meal was improved by thermal processes. The autoclaving might serve as a tool for ANFs reduction. While, extrusion cooking could improve in vitro protein digestibility, antioxidant activities and functional properties of sacha inchi meal. The sacha inchi meal through thermal processes might be helpful to produce highly nutritious foods, alternative protein related products and enhance its suitability as novel functional ingredients for the food system for industrial applications.